Tabata protocol-based high-intensity interval training in freestyle wrestlers - Kolimechkov, S.; Makaveev, R.; Zaykova, D.; Petrov, L. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. The physical attributes of muscular strength and endurance are essential for wrestlers to perform successfully. For the development of these physical qualities, high intensity interval training (HIIT) using kettlebell strength exercises is appropriate. The purpose of this study was to develop a kettlebell HIIT program for wrestlers and evaluate the results on strength and endurance.